2006
DOI: 10.1103/physrevlett.97.067403
|View full text |Cite
|
Sign up to set email alerts
|

Trapped Electromagnetic Modes and Scaling in the Transmittance of Perforated Metal Films

Abstract: We describe measurements and simulations of the enhanced transmittance by subwavelength hole arrays in silver films. The array period and hole size are systematically varied to give peak transmittances at wavelengths spanning a factor of 14. The spectra coincide when scaled using the array geometry and substrate refractive index alone, thus showing no significant dependence on the dielectric function of the metal. We argue that the spectra can be explained by interference of diffractive and resonant scattering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 24 publications
(19 reference statements)
1
14
0
Order By: Relevance
“…There is a renewed interest in electromagnetic FP resonances, especially their relevance to the recently observed transmission enhancement through subwavelength openings in normally opaque objects, [1][2][3][4][5][6][7][8] as well as to the ensuing debate on the relative contributions of surface wave versus diffraction in such phenomena. [9][10][11][12][13][14][15][16][17][18][19] It has been shown that light transmission through hole arrays in perfect-conductor thin films, where there can be no true surface waves, may be attributed ͑via Babinet's principle͒ to the reflection by the complementary structure consisting of planar arrays of perfect-conductor disks. 17,18 Transmission can always reach unity at some resonant wavelengths regardless of how small the holes are, while the complementary system can exhibit perfect reflection for arbitrarily small disks.…”
Section: Introductionmentioning
confidence: 99%
“…There is a renewed interest in electromagnetic FP resonances, especially their relevance to the recently observed transmission enhancement through subwavelength openings in normally opaque objects, [1][2][3][4][5][6][7][8] as well as to the ensuing debate on the relative contributions of surface wave versus diffraction in such phenomena. [9][10][11][12][13][14][15][16][17][18][19] It has been shown that light transmission through hole arrays in perfect-conductor thin films, where there can be no true surface waves, may be attributed ͑via Babinet's principle͒ to the reflection by the complementary structure consisting of planar arrays of perfect-conductor disks. 17,18 Transmission can always reach unity at some resonant wavelengths regardless of how small the holes are, while the complementary system can exhibit perfect reflection for arbitrarily small disks.…”
Section: Introductionmentioning
confidence: 99%
“…The role of SPPs on EOT has been debated vigorously in the literature [31][32][33][34][35][36][37][38][39]. Some works have suggested that the diffraction of many evanescent modes is required to fully-explain the transmission, and the single SPP description is not sufficient.…”
Section: Real Metals At Different Wavelengthsmentioning
confidence: 99%
“…EOT has been reported in one-and two-dimensional gratings in numerous theoretical and experimental studies [3][4][5][6][7][8] and over a wide range of wavelengths. 9,10 Several mechanisms have been identified that contribute to EOT, such as surface plasmon resonances, 11,12 cavity resonances, 13 and dynamical diffraction, 4 all of them describable using a simple analytical formulation. 13 Similar to light, the wave nature of sound can be exploited to produce extraordinary acoustic transmission, which has been recently studied in one-͑slit͒ and twodimensional ͑hole͒ apertures.…”
mentioning
confidence: 99%